High free testosterone index increases lung function in adult males - Martiem Mawi; Rully Ayu Nirmalasari (Faculty of Medicine, Universitas Trisakti, 2012)
BackgroundIncreasing age and decreased testosterone concentrations in males influence muscle strength and muscle mass, particularly in skeletal muscle. There have been few studies on decreased lung function resulting from reduced mass and strength of respiratory muscles. The aim of the present study was to investigate the existence of an association between free testosterone index (FTI) and lung function in males aged between 40 and 80 years.MethodsThis cross-sectional study involved 167 males aged between 40 and 80 years in Cilandak subdistrict, South Jakarta. Total serum testosterone and sex hormone-binding globulin (SHBG) concentrations were determined by electrochemiluminescence immunoassay (ECLIA) using Roche Elecsys Reagent Kit Cat 11776061 and Elecsys 2010 reagent (Cobas e601), respectively FTI was calculated using the formula free testosterone/SHBG x 100%. Forced expiratory volume in 1 second (VEP1) was assessed by means of an AS 500 spirometer. ResultsMean age of the subjects was 53.32 ± 8.26 years, mean total serum testosterone concentration was 532.59 ± 206.92 ng/dL, mean SHBG concentration 41.26 ± 21.14 nmol/L, mean FTI 48.22 ± 14.34 %, and mean VEP1 was 1.63 ± 0.54 L. There was a significant association between both SHBG and FTI on the one hand and VEP1 on the other, with Pearson correlation coefficients of -0.199 (p=0.010) and 0.271 (p=0.000), respectively. Linear multiple regression analysis indicated that FTI was the most influential variable on lung function (VEP1), higher FTI values indicating higher VEP1 (â=0.008: p=0.004).ConclusionIn males aged 40-80 years, higher FTI values indicate better lung function as determined by means of VEP1.